Optimizing Management Decisions: Special Order Pricing in MSMEs: Menganalisis Biaya Diferensial dalam Pengambilan Keputusan Manajemen: Studi Kasus pada Penentuan Harga Pesanan Khusus di UMKM - Arum Ambarsari; Wisnu Panggah Setiyono (Universitas Muhammadiyah Sidoarjo, 2023)
This study employs a descriptive quantitative research approach to analyze and test the application of the Analysis of Differential Costs in management decision making regarding the acceptance or rejection of special order prices in MSMEs. Data was collected through interviews and questionnaires, and the analysis focused on the differential costs incurred by Kedai Vivi, a representative MSME, in relation to alternative products. The results of the analysis indicated that accepting special orders in November 2021 yielded a profit of Rp. 1,119,800 for Kedai Vivi, while rejecting the special order would result in a profit of only Rp. 915,790. The findings highlight a positive differential profit, indicating that the differential cost was lower than the selling price set by MSME Kedai Vivi. This study provides valuable insights into the effective utilization of differential cost analysis in supporting management decision making within MSMEs, with implications for enhancing profitability and competitiveness in the global market. Highlights: Differential cost analysis: Examining the differences in costs associated with alternative products or decisions, enabling informed management decision making. Special order pricing: Investigating the impact of accepting or rejecting special orders on profitability, considering factors such as selling price and differential costs. MSMEs and profitability: Exploring the implications of effective cost analysis and decision making for small and medium-sized enterprises, enhancing their profitability and competitiveness. Keywords: Differential costs, Management decision making, Special order pricing, MSMEs, Profitability analysis